Pengolahan Data Arsip Dinamis Inaktif Hukum Menggunakan Microsoft Access di Kantor Pengadilan Negeri Payakumbuh - Vanny, Rahmadya; Syahyuman, Syahyuman (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of writing this paper is to describe how the data processing inactive records law by using the Microsoft Access program at the Office of State Court Payakumbuh. The method used in writing this paper is the observation and direct participation by collecting data from the original source data list files written in a register clerk. Microsoft Access use data processing performed on the data file received from October to December of 2011, amounting to 110 archival data, consisting of a data file civil cases and criminal cases archived data. The treatment process begins with mengentri data into the table in Microsoft Access and create a Query. Query was created as a tool to search the data, because queries can answer questions on the data in question. Making Query in Microsoft Access only put one formula on Parameter Query and Query straight to work. Working with Query makes the search easy and fast.